A SYSTEMATIC LITERATURE REVIEW: PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Rakuty Ardan Permadi; Novita Sari; Hidayat Jati; Riyan Sisiawan Putra; Nuzulul Fatimah (P3M STIE Mulia Darma Pratama, 2026)
Employee performance is one of the key factors determining an organization's success in achieving its objectives. Previous studies have shown that compensation and work motivation influence employee performance; however, the findings remain inconsistent across different organizational contexts. Therefore, this study aims to analyze the effect of compensation on employee performance, the effect of work motivation on employee performance, and the simultaneous effect of both variables on employee performance. This study employed a Systematic Literature Review (SLR) approach by collecting and analyzing scientific articles obtained through Google Scholar based on predetermined inclusion and exclusion criteria. A total of 22 articles met the eligibility criteria and were included in the review process. The findings indicate that compensation generally has a positive and significant effect on employee performance by enhancing job satisfaction and work enthusiasm. Work motivation was also found to have a positive and significant effect on employee performance through increased commitment, productivity, and responsibility. Furthermore, compensation and work motivation simultaneously contribute more effectively to improving employee performance than when applied separately. This study concludes that compensation and work motivation are strategic factors that should be managed effectively to improve employee performance and support organizational goals